Pre-exercise Caffeine Intake Enhances Bench Press Strength Training Adaptations - Giráldez-Costas, Verónica; Ruíz-Moreno, Carlos; González-García, Jaime; Lara, Beatriz; Del Coso, Juan; Salinero, Juan José (Frontiers in Nutrition, 2021)
Previous research has identified acute caffeine intake as an effective ergogenic aid to enhance velocity and power during bench press exercise. However, no previous investigation has analyzed the effects of chronic intake of caffeine on training adaptations induced by bench press strength training. Thus, the aim of this investigation was to determine the effects of pre-exercise caffeine intake on training adaptations induced by a bench press training protocol. Using a double-blind, randomized experimental design, 16 healthy participants underwent a bench press training protocol for 4 weeks (12 sessions). Seven participants ingested a placebo and nine participants ingested 3 mg/kg/BM of caffeine before each training session. Three days before, and 3 days after the completion of the training protocol, participants performed a one-repetition maximum (1RM) bench press and force-velocity test (from 10 to 100% 1RM). From comparable pre-training values, the strength training similarly increased 1RM in the caffeine and placebo groups (+13.5 ± 7.8% vs. +11.3 ± 5.3%, respectively; p = 0.53). In the caffeine group, the strength training induced a higher mean velocity at 40%, (0.81 ± 0.08 vs. 0.90 ± 0.14 m/s), 60% (0.60 ± 0.06 vs. 0.65 ± 0.06 m/s), 70% (0.47 ± 0.05 vs. 0.55 ± 0.06 m/s), 80% (0.37 ± 0.06 vs. 0.45 ± 0.05 m/s), 90% (0.26 ± 0.07 vs. 0.34 ± 0.06 m/s), and 100% 1RM (0.14 ± 0.04 vs. 0.25 ± 0.05 m/s; p < 0.05) while the increases in the placebo group were evident only at 30 (0.95 ± 0.06 vs. 1.03 ± 0.07 m/s), 70% (0.51 ± 0.03 vs. 0.57 ± 0.05 m/s) and 80% 1RM (0.37 ± 0.06 vs. 0.45 ± 0.05 m/s) (p < 0.05). The placebo group only increased peak velocity at 60 and 70% 1RM (p < 0.05) while peak velocity increased at 10%, and from 30 to 100% 1RM in the caffeine group (p < 0.05). The use of 3 mg/kg/BM of caffeine before exercise did not modify improvements in 1RM obtained during a 4 week bench press strength training program but induced more muscle performance adaptations over a wider range of load.